Perancangan Alat Panca Indera Manusia untuk Media Pembelajaran Menggunakan Teknologi Augmented Reality untuk Jenjang Sekolah Dasar - Ayu Latifah; Asri Mulyani; Fahru Nisa Aulia (Institut Teknologi Garut, 2022)
In the world of education, especially in the delivery of material in school activities, it is necessary to contain interactive and even challenging aspects to be able to provide new experiences for teachers and students, natural science subjects, especially those related to the introduction of the five senses, is one of the materials that can adopt the media. learning by using one of the interactive multimedia technologies because the five senses are the most important tools in humans. However, in learning media that still uses book teaching techniques and seems bored, many children do not really understand this sensory material. The purpose of making applications for the five senses is using Augmented Reality technology which can help the learning process of elementary school students because it has an attractive visual appearance. The method used is the Multimedia Development Life Cycle with several stages taken in related methods starting with concept, then design, then data collection, then assembly, testing, and finally distribution. With the application of learning tools for the human senses that can be accessed in a mobile manner, it allows students to be able to do learning anywhere and anywhere, so that it is expected to increase students' understanding of learning material, especially regarding the introduction of the five human senses.